The Effect of Product Quality, Price Perception, and Promotion on Consumer Purchase Decisions for Cleo Brand 550 Ml Packaging Mineral Water - Sisilia Putri K.D; Siti Ning Farida (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of product quality, price perception, and promotion on consumer decisions in purchasing 550 ml of Cleo brand mineral water. In an era of tight competition in the bottled drinking water industry, understanding the factors that influence purchasing decisions is crucial for companies to maintain and increase market share. This study uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents who are active consumers of the Cleo brand. The data analysis technique used is multiple linear regression. The results of the study indicate that product quality, price perception, and promotion simultaneously have a significant effect on consumer purchasing decisions. Partially, product quality and price perception have a positive and significant effect, while promotion shows a lower but still significant effect. These findings provide important implications for Cleo's marketing strategy, especially in maintaining quality and setting prices that are in accordance with consumer value perceptions.